«Axí com...» Le comparazioni nella lirica di Jordi de Sant Jordi - Scarpati, Oriana (Caplletra. Revista Internacional de Filologia, 2005)
Jordi de Sant Jordi uses more than thirty comparisons in his lyric poetry. These may be classified on the basis of their typology and semantic functions: true comparisons (where two elements are compared by means of a connector, the firstbeing defined as ‘real’ and corresponding to the situation of the lyric persona, the second, figurative, presenting in metaphorical terms the same characteristics as the firstelement); comparisons between the ‘real’ situation and that of an unspecified human being, to which reference is made by means of the demonstrative ‘the one’ («axí com cell...»); hyperbolic comparisons, where the ‘real’ element is given hyperbolically as having to the same or to a greater extent a quality for which the second element is the example par excellence (‘stronger than Hercules’). Finally, we have identified a particular figure —which we have called an ‘abbreviated priamel’— whereby two situations are given between which the lyric persona must choose, stating that it prefers one and not the other.